The Predicament of Traditional Femininity: A Gender Material Culture Analysis of Civil War Blockade Runners - Schwalbe, Emily Anne (East Carolina University, 2016)
This thesis will seek to examine the tension between nineteenth-century Southern gender expectations of upper-class femininity contrasted with the necessities of wartime and determine if this tension is evident in the material record by analyzing the cargo of Confederate blockade runners entering the affluent ports of Wilmington and Charleston. By examining the cargo from blockade runners, as well as analyzing historical records, research will lead to conclusions about what women wanted to buy during the Civil War. It will compare these demands with the new notions of simplicity and sacrifice that theoretically defined the Confederacy, in order to better understand gender expectations during this period.
Keywords: Gender Archaeology; Blockade Runners; United States--History--Civil War, 1861-1865--Women; Material culture--Southern States--History; Social status--Southern States--History; Sex role--Southern States--History